2016
DOI: 10.1002/jclp.22407
|View full text |Cite
|
Sign up to set email alerts
|

Which Homeless Veterans Benefit From a Peer Mentor and How?

Abstract: The majority of Veteran participants in this study benefited from receiving peer mentor intervention. African American Veterans were more likely to benefit and Veterans with PTSD were less likely to benefit. Client endorsement of the peer's role influenced outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Although the exact job tasks of peer navigators vary by location, in general, VA peer navigators are veterans who have experience with homelessness and/or with navigating the VA health care system and can therefore serve as resources for their peers. These peer support resources have shown promise in supporting African American homeless veterans [ 86 ]: one study in particular found that homeless African Americans perceived peer navigators to be a useful source of practical logistical information and a resource for troubleshooting creative ways to engage meaningfully in the health system [ 87 ]. Another study on peer navigators found that ninety percent of homeless veterans accessing peer navigator services identified as members of minority groups; when peer navigators share demographic characteristics and identities with those they serve, veterans may feel more trusting and be more amenable to accessing care [ 56 ].…”
Section: Barriers To Access and Interventions/tools By Dimensionmentioning
confidence: 99%
“…Although the exact job tasks of peer navigators vary by location, in general, VA peer navigators are veterans who have experience with homelessness and/or with navigating the VA health care system and can therefore serve as resources for their peers. These peer support resources have shown promise in supporting African American homeless veterans [ 86 ]: one study in particular found that homeless African Americans perceived peer navigators to be a useful source of practical logistical information and a resource for troubleshooting creative ways to engage meaningfully in the health system [ 87 ]. Another study on peer navigators found that ninety percent of homeless veterans accessing peer navigator services identified as members of minority groups; when peer navigators share demographic characteristics and identities with those they serve, veterans may feel more trusting and be more amenable to accessing care [ 56 ].…”
Section: Barriers To Access and Interventions/tools By Dimensionmentioning
confidence: 99%
“…That said, there is some evidence that curricular attention to homelessness can moderately improve attitudes toward patients experiencing homelessness among trainees (Buchanan et al, 2004). And other work suggests that patient-level peers can have positive impacts on behavioral health, and on primary care in VA’s Homeless Patient Aligned Care Teams (Barker & Maguire, 2017; Resnik et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of peer mentorship for veterans enrolled in primary care who were living on the street or in temporary shelters, Resnik et al (2017) reported a nonsignificant effect of the program on participants' social support. The authors indicated that implementation issues may have influenced the result, for example, the peer support intervention may have been too brief for a relationship to develop between peer support workers and service users, and peer support workers may have lacked the knowledge required to help service users to navigate health and shelter services (Resnik, Eckerholm, Johnson, Ellison, & O'Toole, 2017).…”
Section: Relational Antecedentsmentioning
confidence: 99%